Fish self-awareness: limits of current knowledge and theoretical expectations - Hubená, Pavla; Horký, Pavel; Slavík, Ondřej (Animal cognition, 2022)
Animal self-awareness is divided into three levels: bodily, social, and introspective self-awareness. Research has focused mainly on the introspection of so-called higher organisms such as mammals. Herein, we turn our attention to fish and provide opinions on their self-awareness based on a review of the scientific literature. Our specific aims are to discuss whether fish (A) could have a neural substrate supporting self-awareness and whether they display signs of (B) social and (C) introspective self-awareness. The present knowledge does not exclude the possibility that fish could have a simple neocortex or other structures that support certain higher cognitive processes, as the function of the primate cerebral cortex can be replaced by other neurological structures. Fish are known to display winner, loser, and audience effects, which could be interpreted as signs of social self-awareness. The audience effect may be explained not only by ethological cost and benefit theory but also by the concept of public self-awareness, which comes from human studies. The behavioural and neural manifestations of depression may be induced in fish under social subordination and may be viewed as certain awareness of a social status. The current findings on fish introspective self-awareness have been debated in the scientific community and, therefore, demand replication to provide more evidence. Further research is needed to verify the outlined ideas; however, the current knowledge indicates that fish are capable of certain higher cognitive processes, which raises questions and implications regarding ethics and welfare in fish-related research and husbandry.
Keywords: Audience; Perception; Winner; percepce; Awareness; zvířata; Mammals; Introspection; motivace; savci; Motivation; Loser; uvědomování si; Subordination; Emotion; Animals